2017
DOI: 10.1002/chem.201701462
|View full text |Cite
|
Sign up to set email alerts
|

Alkynyl N‐Nosylhydrazones: Easy Decomposition to Alknynl Diazomethanes and Application in Allene Synthesis

Abstract: The decomposition of N-tosylhydrazones is a safe and convenient method for the generation of donor carbenes. However, alkynyl carbenes cannot be isolated by this route because they readily undergo intramolecular cyclization to pyrazoles as soon as formed from alkynyl N-tosylhydrazones. Here, the use of alkynyl N-nosylhydrazones for the in situ generation of alkynyl carbenes and their coupling reaction with boronic acids under metal-free conditions is reported, giving rise to a wide array of di- and trisubstitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 73 publications
0
16
0
1
Order By: Relevance
“…[23] This resultw as in sharp contrast to the reactionw ith alkynyl N-tosylhydrazone which providedt he pyrazole under similar reactionc onditions.N otably, the side product of the reaction, alkyne 46,w as converted into the allene by stirring the crude reaction mixture with potassium hydroxide and tetra-n-butylammonium bromide( TBAB). [23] This resultw as in sharp contrast to the reactionw ith alkynyl N-tosylhydrazone which providedt he pyrazole under similar reactionc onditions.N otably, the side product of the reaction, alkyne 46,w as converted into the allene by stirring the crude reaction mixture with potassium hydroxide and tetra-n-butylammonium bromide( TBAB).…”
Section: Reductive Coupling With Boronic Acidsmentioning
confidence: 79%
See 1 more Smart Citation
“…[23] This resultw as in sharp contrast to the reactionw ith alkynyl N-tosylhydrazone which providedt he pyrazole under similar reactionc onditions.N otably, the side product of the reaction, alkyne 46,w as converted into the allene by stirring the crude reaction mixture with potassium hydroxide and tetra-n-butylammonium bromide( TBAB). [23] This resultw as in sharp contrast to the reactionw ith alkynyl N-tosylhydrazone which providedt he pyrazole under similar reactionc onditions.N otably, the side product of the reaction, alkyne 46,w as converted into the allene by stirring the crude reaction mixture with potassium hydroxide and tetra-n-butylammonium bromide( TBAB).…”
Section: Reductive Coupling With Boronic Acidsmentioning
confidence: 79%
“…Although the whole discussion is centred on N ‐tosylhydrazones, it is worthy to note here the reactivity of N ‐nosylhydrazone which are able to decompose at room temperature to realize the in situ generation of carbenes. The coupling between alkynyl N ‐nosylhydrazones 44 and boronic acids under metal‐free conditions furnished the di‐ and trisubstituted allenes 45 (Scheme ) . This result was in sharp contrast to the reaction with alkynyl N ‐tosylhydrazone which provided the pyrazole under similar reaction conditions.…”
Section: C−c Bond Formationsmentioning
confidence: 96%
“…21 In this context, Bi, Zanoni et al reported the reaction of alkynyl N-nosylhydrazones with boronic acids, that led to the formation of allenes. 22 The reaction takes advantage of the ability of N-nosylhydrazones to undergo decomposition at lower temperatures than N-tosylhydrazones, preventing the intramolecular cyclization and allowing the intermolecular reaction with the boronic acid (Scheme 22). Under the optimized conditions the reaction features a remarkable scope, as both alkyl and arylboronic acids can participate in the coupling process.…”
Section: Synthesis Of Allenes By Reactions With Alkynyl Nnosylhydrazonesmentioning
confidence: 99%
“…The final treatment with KOH/TBAB isomerizes the alkyne 73 into the allene 72. According to the authors, 22 both protodeboronation pathways operate, representing an unprecedented example of γ-protodeboronation of propargylboronic derivatives (Scheme 24).…”
Section: Scheme 21 Justification Of the Observed Stereochemistry Based On Dft Computations 5 Synthesis Of Allenes By Reactions With Alkynmentioning
confidence: 99%
“…然而, 炔基醛衍生的 N-对甲基苯磺酰腙在碱性 条件下, 很难通过分解的方法获得炔基卡宾化合物, 而 是发生分子内[3+2]环合反应生成吡唑化合物 [24] . 2017 年, 我们课题组 [25] 6 Reactions of aromatic aldehyde derivated N-o-nitrophenylsulfonylhydrazones with α-diazo esters, amides and phosphonates 图 7 炔基醛衍生的 N-邻硝基苯磺酰腙与硼酸的反应 Figure 7 Reactions of alkynyl aldehyde derivated N-o-nitrophenylsulfonylhydrazones with boronic acids 随后, 我们课题组 [26] [17] , 采用氟代羰 基化合物衍生的 N-邻三氟甲基苯磺酰腙作为原料, 可 以在碱性条件下原位生成氟代重氮乙烷. 2019 年, 我们 课题组 [28] [33] .…”
unclassified